Development of high mobility in-pipe inspection robot - Woongsun Jeon; Jungwan Park; Inho Kim; Yoon-Koo Kang; Hyunseok Yang (2011 IEEE/SICE International Symposium on System Integration, 2011)
In this paper, we propose a steerable inchworm type in-pipe inspection robot. An extensor mechanism using continuum links makes the robot possible for both steering and inchworm locomotion. The robot has two clamper modules which are composed of a crank-slider mechanism. The mechanism makes the robot compact and adaptable to pipe diameter change from 205mm to 305mm. We also analyzed steering locomotion of the robot and propose a simple strategy for navigating in a T-branch pipe. The mechanisms and strategy are demonstrated by experiment.